No recovery of campo rupestre grasslands after gravel extraction: implications for conservation and restoration - Le Stradic, Soizig; Fernandes, Geraldo W.; Buisson, Elise (Restoration ecology, 2018)
Old‐growth grasslands, including savannas and tropical grasslands, need centuries to assemble; they are therefore expected to have low resilience to anthropogenic activities that disturb the soil (e.g. cultivation, quarrying, mining, etc.). Understanding which parameters restrict the natural recovery of degraded ecosystems is a major prerequisite for planning an effective restoration program. This study was designed to evaluate the recovery of an old‐growth grassland, the campo rupestre, after a major disturbance: gravel extraction. In 2010 (i.e. 8 years after the degradation), we analyzed soil characteristics, seed bank, and vegetation composition in degraded sites consisting of sandy or gravel substrates, as well as in reference sites of sandy and gravel grasslands. At degraded sites, soils contained lower concentrations of the main nutrients, and seed banks consisted mainly of nontarget species. Seed banks of reference grasslands were poor in species and in seeds. Eight years after the degradation, plant communities at degraded sites were still very different from those at the reference sites, with ruderals and almost no target species. Altered soil conditions, low capacity of campo rupestre species to form seed banks, and the probable restriction of seed dispersal from the target species in nearby campo rupestre considerably limited the establishment of campo rupestre plant communities in degraded areas. Time is essential for old‐growth grassland assemblage and, even with the presence of a propagule source in the surroundings, the assembly of campo rupestre plant communities in degraded sites will take centuries. Therefore, human intervention is necessary to rapidly reestablish the main species.